Trends in risk factors for coronary heart disease in the Netherlands - C. Koopman; I. Vaartjes; A. Blokstra; W. M. M. Verschuren; M. Visser; D. J. H. Deeg; M. L. Bots; I. van Dis (BMC, 2016)
Abstract Background Favourable trends in risk factor levels in the general population may partly explain the decline in coronary heart disease (CHD) morbidity and mortality. Our aim was to present long-term national trends in established risk factors for CHD. Methods Data were obtained from five data sources including several large scale population based surveys, cohort studies and general practitioner registers between 1988 and 2012. We applied linear regression models to age-standardized time trends to test for statistical significant trends. Analyses were stratified by sex and age (younger <65 and older ≥65 years adults). Results The results demonstrated favourable trends in smoking (except in older women) and physical activity (except in older men). Unfavourable trends were found for body mass index (BMI) and diabetes mellitus prevalence. Although systolic blood pressure (SBP) and total cholesterol trends were favourable for older persons, SBP and total cholesterol remained stable in younger persons. Conclusions Four out of six risk factors for CHD showed a favourable or stable trend. The rise in diabetes mellitus and BMI is worrying with respect to CHD morbidity and mortality.